1 2 5 y 2 = 1 0 8 x 3 + 5 0 0 How many ordered pairs of integers ( x , y ) satisfy the above equation?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Kazem Sepehrinia , congrats on having 500 followers!
I can't understand your line '9 - 36(1 - c^2)=k^2'.And how did you get this 'k' ?Please explain in detail.
What about (-1.667,0) ? Set y = 0 in the above equation. Then 108x^3 = -500 x = -1.667
Certainly x must be a multiple of 5 , and y must be a multiple of 2 . Writing x = 5 X and y = 2 Y we obtain that Y 2 = 2 7 X 3 + 1 so that a = 3 X , b = Y is a solution of the Diophantine equation b 2 = a 3 + 1 .
Euler proved that the only solutions in integers of this equation are ( 0 , 1 ) , ( 0 , − 1 ) , ( − 1 , 0 ) , ( 2 , 3 ) , ( 2 , − 3 ) . Since we need a to be a multiple of 3 , we see that only the first two of these are relevant. Thus the only solutions to the original equation are x = 0 , y = ± 2 , and so the answer is 2 .
Problem Loading...
Note Loading...
Set Loading...
Observe that y is even. let y = 2 b 1 2 5 b 2 = 2 7 x 3 + 1 2 5 It follows that 1 2 5 ∣ 2 7 x 3 and 5 ∣ x , so let x = 5 a equation becomes b 2 = 2 7 a 3 + 1 = ( 3 a + 1 ) ( 9 a 2 − 3 a + 1 ) Now, let d be the greatest common divisor of two factors in the RHS of this equation. We have d ∣ 9 a 2 − 3 a + 1 − 3 a ( 3 a + 1 ) = − 6 a + 1 ⟹ d ∣ − 6 a + 1 + 2 ( 3 a + 1 ) = 3 ⟹ d ∣ 3 Therefore, d = 1 or d = 3 , but 3 a + 1 ≡ 9 a 2 − 3 a + 1 ≡ 1 ( m o d 3 ) , so d = 1 . Note that product of two relatively prime factors is a perfect square. Hence both of them must be squares and specially 9 a 2 − 3 a + 1 = c 2 Discriminant of this quadratic in terms of a must be a perfect square too, this means 9 − 3 6 ( 1 − c 2 ) = k 2 ⟹ ( 6 c − k ) ( 6 c + k ) = 2 7 One can easily find out that c = ± 1 and 9 a 2 − 3 a + 1 = c 2 = 1 ⟹ 9 a 2 − 3 a = 0 ⟹ a = 0 Which gives x = 0 and 1 2 5 y 2 = 5 0 0 or y 2 = 4 . Thus the solutions are ( x , y ) = ( 0 , − 2 ) , ( 0 , 2 ) .